2012
DOI: 10.1128/mcb.00436-12
|View full text |Cite
|
Sign up to set email alerts
|

Nek4 Regulates Entry into Replicative Senescence and the Response to DNA Damage in Human Fibroblasts

Abstract: c When explanted into culture, normal human cells exhibit a finite number of cell divisions before entering a proliferative arrest termed replicative senescence. To identify genes essential for entry into replicative senescence, we performed an RNA interference (RNAi)-based loss-of-function screen and found that suppression of the Never in Mitosis Gene A (NIMA)-related protein kinase gene NEK4 disrupted timely entry into senescence. NEK4 suppression extended the number of population doublings required to reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 55 publications
1
43
0
Order By: Relevance
“…2). In addition, thermal stress and the combined stress treatment significantly changed serine/threonine-protein kinase Nek4 isoform X5 (Nek4) expression, which potentially affects threonine residues, and is required for normal cell cycle arrest in response to double-stranded DNA damage (Nguyen et al, 2012). All the evidence showed that the cell cycle process was extensively changed when sea cucumbers were exposed to environmental stress.…”
Section: Discussionmentioning
confidence: 99%
“…2). In addition, thermal stress and the combined stress treatment significantly changed serine/threonine-protein kinase Nek4 isoform X5 (Nek4) expression, which potentially affects threonine residues, and is required for normal cell cycle arrest in response to double-stranded DNA damage (Nguyen et al, 2012). All the evidence showed that the cell cycle process was extensively changed when sea cucumbers were exposed to environmental stress.…”
Section: Discussionmentioning
confidence: 99%
“…AURKA and CHK1 are being pursued as drug targets (3537), while NEK4 a member of the NIMA family of kinases modulates sensitivity to microtubule poisons and DNA damage (3840). …”
Section: Discussionmentioning
confidence: 99%
“…The clear function and involvement of NEK4 in cellular processes are yet to be determined, but it is suggested that NEK4 participates in primary cilium assembly, regulation of microtubule stabilization [25], the DNA damage response (DDR) [31], and RNA splicing [18]. A second functional isoform [18], which is similar to the murine NEK4 long isoform and named NEK4.2, has been identified in humans, and different interactors to NEK4.1 have been described.…”
Section: Nek4mentioning
confidence: 99%